Unravelling chemical priming machinery in plants: the role of reactive oxygen–nitrogen–sulfur species in abiotic stress tolerance enhancement - Antoniou, Chrystalla; Savvides, Andreas M.; Christou, Anastasis; Fotopoulos, Vasileios (My University, 2016)
Abiotic stresses severely limit crop yield and their detrimental effects are aggravated by climate change. Chemical priming is an emerging field in crop stress management. The exogenous application of specific chemical agents before stress events results in tolerance enhancement and reduction of stress impacts on plant physiology and growth. However, the molecular mechanisms underlying the remarkable effects of chemical priming on plant physiology remain to be elucidated. Reactive oxygen, nitrogen and sulfur species (RONSS) are molecules playing a vital role in the stress acclimation of plants. When applied as priming agents, RONSS improve stress tolerance. This review summarizes the recent knowledge on the role of RONSS in cell signalling and gene regulation contributing to abiotic stress tolerance enhancement.
Keywords: Medicago-truncatula-plants; Nitric-oxide; Hydrogen-sulfide; Sodium-nitroprusside; Salt-stress; Transcriptional regulation